2012
DOI: 10.1117/12.912190
|View full text |Cite
|
Sign up to set email alerts
|

Nonrigid registration and classification of the kidneys in 3D dynamic contrast enhanced (DCE) MR images

Abstract: We have applied image analysis methods in the assessment of human kidney perfusion based on 3D dynamic contrast-enhanced (DCE) MRI data. This approach consists of 3D non-rigid image registration of the kidneys and fuzzy C-mean classification of kidney tissues. The proposed registration method reduced motion artifacts in the dynamic images and improved the analysis of kidney compartments (cortex, medulla, and cavities). The dynamic intensity curves show the successive transition of the contrast agent through ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
(26 reference statements)
0
37
0
Order By: Relevance
“…In addition, registration is a necessary step to correct the effect of kidney motion, and nonrigid registration is more accurate. Many image registration algorithms show their application prospect …”
Section: Renal Fmrimentioning
confidence: 99%
“…In addition, registration is a necessary step to correct the effect of kidney motion, and nonrigid registration is more accurate. Many image registration algorithms show their application prospect …”
Section: Renal Fmrimentioning
confidence: 99%
“…In a postprocessing step, image registration algorithms [12] can be employed to address the movement. A new algorithm of 3D non-rigid image registration of the kidneys based on 3D dynamic contrast-enhanced MRI data proposed by Yang et al [13] showed an optimum application prospect. In our study, patients to be trained to breathe slightly (as possible as thoracic breathing) and sand bag were put on the abdomen to deduce the upper abdomen movement led by breath, and the breath artifacts were evidently deduced.…”
Section: Motion Correctionmentioning
confidence: 99%
“…Many registration methods have been developed for the alignment of DCE-MRI of organs such as the heart and kidneys (11). However, these methods cannot be directly applied to current vascular DCE-MRI protocols, because of the small size of the carotid arteries (less than 1 cm in diameter) with respect to other organs, and the prominent use of two-dimensional (2D) multislice, instead of 3D volumetric, acquisitions (12).…”
mentioning
confidence: 99%